Basal cell carcinoma in the elderly Cryosurgery or surgery - a case study with reference to the literature - Kamil Kapłon; Laura Wojtala; Weronika Pawlak; Weronika Pawłocik; Lena Musiał; Agnieszka Możdżyńska; Julia Szymańska; Ewa Grabowska; Anna Rymarz; Dominika Kojder (Kazimierz Wielki University, 2023)
Introduction The aging of society leads to an increase in the occurrence of basal cell carcinoma (BCC). BCC includes both superficial and nodular lesions with a good prognosis as well as foci that are difficult to treat and require a multidisciplinary approach. There are two basic methods of treating BCC, surgery to remove the tumor and cryosurgery. The paper presents a case of an 82-year-old female patient suffering from BCC in a non-advanced stage of the disease with the presentation of subsequent stages of treatment. Aim of the study An attempt was made to confront an alternative method of BCC treatment by cryosurgery with the first-choice procedure - surgical excision of the tumor with a margin of healthy tissues. Description of the case An individual clinical case study including the patient's medical records. Conclusions The work emphasizes the importance of comprehensive care for a patient diagnosed with BCC. Individualization of the diagnostic and therapeutic process is the basis for dealing with the elderly patient.